Development of the Consolidated Navigation System - Debrecht, Steven J. (The International Hydrographic Review, 2015)
The Defense Mapping Agency (DMA) has recently taken a major step into a ‘paperless’ production process. Notice to Mariners corrections are no longer printed on a card, passed along for review and evaluation, and batch loaded into the computer. Terminal input and soft copy screen edit allow for maximum flexibility, clarity, and consistency.